Scientific Development Based on Unity of Sciences (Waḥdat Al-‘Ulum) Paradigm - Mirza Mahbub Wijaya; Mahfud Junaedi; Sholihan Sholihan (International Journal Ihya' 'Ulum al-Din, 2021)
This study aims to determine the systematic and fundamental philosophical foundation of Walisongo State Islamic University (UIN). This research uses a philosophical and historical approach and content analysis method to obtain information in depth. Begins with data collection through literature studies, documents are related to it. The scientific integration of the Unity of Sciences paradigm in the scientific cluster being developed contains three strategies that try to answer. The first is the science of religion that is not down to earth or lacks benefits for the wider community. Then the second is when modern sciences are tasteless and value-free. The last is the local culture which began to fade with the development of modernization. These problems will be answered with the humanization of Islamic sciences, the spiritualization of modern sciences, and the revitalization of local wisdom. Scientific development in the clumps of Islamic sciences produces religious knowledge following the times, not rigid and friendly to local wisdom. Meanwhile, the natural sciences and social humanities are planted with spiritual values. Thus, this research can be used as a stepping stone or a model for scientific integration at the State Islamic Institute (IAIN) to shift to the State Islamic University (UIN).